Analysis of polyclonal and monoclonal antibody to the influenza virus nucleoprotein in different oligomeric states - Mallory L. Myers; Michael T. Conlon; John R. Gallagher; De'Marcus D. Woolfork; Noah D. Khorrami; William B. Park; Regan K. Stradtman-Carvalho; Audray K. Harris (Virus Research)
Influenza virus nucleoprotein (NP) is one of the most conserved influenza proteins. Both NP antigen and anti-NP antibodies are used as reagents in influenza diagnostic kits, with applications in both clinical practice and influenza zoonotic surveillance programs. Despite this, studies on the biochemical basis of NP diagnostic serology and NP epitopes are not as developed as for hemagglutinin (HA), the fast-evolving antigen which has been the critical component of current influenza vaccines. Here, we characterized the NP serology of mice, ferrets, and human sera and the immunogenic effects of NP antigen presented as different structural complexes. Furthermore, we show that the classical mouse anti-NP mAb HB65 could detect NP in some commercial influenza vaccines. MAb HB65 bound a linear epitope with nanomolar affinity. Our analysis suggests that linear NP epitopes paired with their corresponding characterized detection antibodies could aid in designing and improving diagnostic technologies for influenza viruses.